Dahlia-shaped nickel cobaltate nanowire cluster / foamed nickel composite electrode, preparation method and application thereof

By conducting hydrothermal reaction on the surface of the foam nickel foam, a dahlia-shaped cobalt acid nanowire cluster/foam nickel foam composite electrode was prepared, which solved the problem of poor electrochemical performance of nickel cobalt acid materials, and achieved improvement of specific capacitance and improvement of electrochemical performance.

CN119889945APending Publication Date: 2025-04-25NANJING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510060080.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing nickel cobalt acid materials have problems such as single morphology, low specific surface area and poor electrochemical performance, which limits their application in supercapacitors.

Method used

By conducting hydrothermal reaction on the surface of nickel foam, a dahlia-shaped cobalt acid nickel nanowire cluster/nickel foam composite electrode was prepared, and the specific surface area and electrochemical activity were improved using the special structure of the nanowire cluster.

Benefits of technology

A significant increase in specific capacitance is achieved, providing more electrochemically active sites, and improving the electrochemical performance of supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119889945A_ABST
    Figure CN119889945A_ABST
Patent Text Reader

Abstract

The invention discloses a dahlia-shaped nickel cobaltate nanowire cluster / foamed nickel composite electrode, a preparation method and application thereof, and belongs to the field of electrode material preparation, and the preparation method comprises the following steps: 1, cleaning foamed nickel, and carrying out vacuum drying to obtain clean foamed nickel; step 2, dissolving NiCl2. 6H2O, CoCl2. 6H2O, urea and lauryl sodium sulfate in a mixed solvent of ethanol and water, uniformly stirring, transferring into an inner container of a hydrothermal reaction kettle, then putting clean foamed nickel, and carrying out hydrothermal reaction to obtain a nickel cobaltate precursor / foamed nickel composite electrode; and step 3, calcining the nickel cobaltate precursor / foamed nickel composite electrode, and then performing cleaning and vacuum drying to obtain the dahlia-shaped nickel cobaltate nanowire cluster / foamed nickel composite electrode. The dahlia-shaped nickel cobaltate nanowire cluster directly grows on the surface of the foamed nickel current collector, nanowires with the diameter of about 80 nm are assembled into a dahlia-like cluster structure, and compared with an existing nickel cobaltate material, the dahlia-shaped nickel cobaltate nanowire cluster has larger specific surface area and higher specific capacitance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrode material preparation, in particular to a dahlia-shaped nickel cobaltate nanowire cluster / nickel foam composite electrode, a preparation method and application thereof. Background Art

[0002] With the further development of the new energy industry, people's demand for high-performance and high-capacity energy storage devices has also increased. Supercapacitors (SCs) are a new type of energy storage device between traditional capacitors and secondary batteries. They can be divided into two types according to their charge storage mechanism: double-layer capacitors and pseudocapacitors. Compared with traditional capacitors, supercapacitors have higher energy density; compared with batteries, supercapacitors have faster charging and discharging speeds, longer cycle life and greater power density. They are an important component in the field of electrochemical energy storage devices at this stage, and therefore have received extensive attention and research from scientific researchers.

[0003] Electrode materials are the core components that affect the performance of supercapacitors. There are many materials that can be used in supercapacitors. At present, the most concerned are carbon materials, conductive polymers and metal oxides. Among them, metal oxides can store and release charges through rapid and reversible redox reactions on their electrode surfaces. This process is called pseudocapacitor energy storage mechanism. The nickel cobalt oxide (NiCo2O4) material with a spinel structure can provide more electrons for the Faraday reaction of pseudocapacitors with the help of various valence changes of nickel and cobalt, thereby effectively improving the specific capacitance of supercapacitors. Related studies have shown that factors such as the micromorphology and pore size distribution of nickel cobalt oxide materials can significantly affect their electrochemical properties. The nanoscale electrode material prepared by a specific process has a larger specific surface area, can provide more active sites during electrochemical reactions, can effectively shorten the ion diffusion journey, and improve electrochemical performance. However, the common nickel cobalt oxide materials currently have problems such as single morphology, low specific surface area, and poor electrochemical performance, which seriously restricts their further development and utilization.

[0004] Therefore, in order to improve the electrochemical activity of nickel cobalt oxide materials, it is very meaningful to design a nanomaterial with high specific surface area and excellent structure, which provides more possibilities for the early commercialization of pseudocapacitive supercapacitors. Summary of the invention

[0005] In view of the above problems, the present invention provides a dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode, a preparation method and application thereof. The dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode prepared by the present invention, wherein the dahlia-shaped nickel cobalt oxide nanowire cluster is directly grown on the surface of the nickel foam current collector, and is assembled from nanowires with a diameter of about 80 nm to form a dahlia-like cluster structure, and compared with existing nickel cobalt oxide materials, has a larger specific surface area and a higher specific capacitance.

[0006] Technical solution: A method for preparing a dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode, comprising the following steps:

[0007] Step 1, washing and vacuum drying the nickel foam to obtain clean nickel foam;

[0008] Step 2: Dissolve NiCl2·6H2O, CoCl2·6H2O, urea and sodium dodecyl sulfate in a mixed solvent of ethanol and water, stir evenly and transfer to a hydrothermal reactor, then add clean nickel foam and perform hydrothermal reaction to obtain a nickel cobalt oxide precursor / nickel foam composite electrode;

[0009] Step 3: calcining the nickel cobalt oxide precursor / nickel foam composite electrode, and then washing and vacuum drying to obtain a dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode.

[0010] Preferably, in step 2, the mass ratio of NiCl2·6H2O, CoCl2·6H2O, sodium dodecyl sulfate and urea is 0.24:0.48:(0.025-0.125):0.6; in the mixed solvent of ethanol and water, the volume ratio of ethanol to water is 1:5.

[0011] Preferably, in step 2, the conditions of the hydrothermal reaction are: the hydrothermal temperature is 110° C., and the hydrothermal time is 6 h.

[0012] Preferably, in step 2, when the clean nickel foam is placed, the clean nickel foam is inserted into the gap of the polytetrafluoroethylene disc so that it stands vertically in the inner tank of the hydrothermal reactor to ensure that the mixed solvent completely immerses the nickel foam.

[0013] Preferably, in step 2, the nickel cobalt oxide precursor / nickel foam composite electrode obtained by the hydrothermal reaction is naturally cooled, the nickel foam is repeatedly rinsed with water and anhydrous ethanol, and dried in a vacuum drying oven; the drying temperature is 70° C., and the drying time is 12 hours.

[0014] Preferably, step one is specifically as follows: cutting the nickel foam, ultrasonically cleaning it with hydrochloric acid, ethanol and deionized water in sequence, and vacuum drying it to obtain clean nickel foam; the nickel foam is cut to a size of 10 mm×20 mm, the concentration of hydrochloric acid is 2 M, the ultrasonic time is 10 min each time, the drying temperature is 70°C, and the drying time is 12 h.

[0015] Preferably, in step three, the nickel cobalt oxide precursor / nickel foam composite electrode is placed in a tubular furnace and calcined under the following conditions: temperature 370° C., calcination atmosphere air, calcination time 1.5 h, and heating rate 5° C. / min.

[0016] Preferably, in step three, the calcined composite electrode is placed in anhydrous ethanol and ultrasonicated for 30 seconds, and then washed and vacuum dried to obtain a dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode; the drying temperature is 70° C., and the drying time is 12 hours.

[0017] The composite electrode prepared by the method of the present invention can be used in supercapacitors.

[0018] Beneficial effects:

[0019] 1) Compared with the nitrate raw materials and fluoride additives used in the synthesis of nickel cobalt oxide nanowires in the past, the raw materials used in the present invention are environmentally friendly and low in cost, the synthesis process is simple and efficient, the repeatability is good, the product size is uniform, the purity is high, and it can be extended to the synthesis of other similar spinel structure materials.

[0020] 2) Compared with the common nanoneedles and nanosheets, the composite electrode material prepared by the method of the present invention has a special structure and a higher specific surface area, which can provide more electrochemical active sites and significantly improve the specific capacitance. Moreover, the nanowires themselves are assembled from nanoparticles, with numerous holes on the surface, which is more conducive to the full wetting of the electrolyte, greatly shortening the migration path of ions, effectively improving the electrochemical performance of supercapacitors, and providing a new method for preparing special patterned nickel cobalt oxide microstructures through nanowire self-assembly. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 X-ray diffraction patterns (XRD) of materials prepared in Example 1 and Comparative Examples 1 and 2;

[0022] Figure 2 The following are scanning electron microscope (SEM), transmission electron microscope (TEM) and energy dispersive spectrum (EDS) images of the material prepared in Example 1;

[0023] Figure 3 is a scanning electron microscope image (SEM) of the material prepared in Example 2;

[0024] Figure 4 is a scanning electron microscope image (SEM) of the material prepared in Example 3;

[0025] Figure 5 The following are the scanning electron microscope (SEM), transmission electron microscope (TEM) and energy dispersive spectrum (EDS) images of the material prepared in Comparative Example 1;

[0026] Figure 6 The following are the scanning electron microscope (SEM), transmission electron microscope (TEM) and energy dispersive spectrum (EDS) images of the material prepared in Comparative Example 2;

[0027] Figure 7 Specific surface area and pore size analysis (BET) diagram of the electrode materials prepared in Example 1 and Comparative Examples 1 and 2;

[0028] Figure 8 1 is a cyclic voltammetry (CV) diagram and a constant current charge-discharge (GCD) diagram of Example 1;

[0029] Fig. 9 It is a constant current charge and discharge (GCD) diagram of the composite electrodes prepared in Examples 1 to 3 and Comparative Examples 1 to 2;

[0030] Fig.10 It is a graph showing the variation of mass specific capacitance (Cs) of the composite electrodes prepared in Examples 1 to 3 and Comparative Examples 1 to 2 with current density. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is described in detail below through embodiments, but the protection scope of the present invention is not limited to the embodiments.

[0032] The raw materials and reagents in the following examples and comparative examples are not specifically stated. The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials can be obtained from commercial sources unless otherwise specified. The nickel foam treatment methods in the following examples and comparative examples are:

[0033] The nickel foam was cut into a size of 10 mm × 20 mm (the thickness of the nickel foam was 1.5 mm), and ultrasonically immersed in a 2M hydrochloric acid solution for 15 min. It was then repeatedly cleaned three times with deionized water and ethanol, and vacuum dried at 70°C for 12 h.

[0034] Example 1: Preparation of dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode-1 (NCO-w1 / NF)

[0035] ① Dissolve 0.24g of NiCl2·6H2O, 0.48g of CoCl2·6H2O, 0.075g of sodium dodecyl sulfate and 0.6g of urea in a mixed solvent of 30mL of ethanol and water, with a volume ratio of ethanol to water of 1:5, and stir thoroughly to make it uniform. Then transfer it to a reactor with a volume of 75mL, use a polytetrafluoroethylene disc with a gap to fix the nickel foam (one piece) to keep it standing vertically in the reactor liner, and hydrothermally react at 110°C for 6h. After the reaction, wash the nickel foam repeatedly with deionized water and ethanol, and vacuum dry it to obtain a nickel cobalt oxide precursor / nickel foam composite electrode;

[0036] ② The nickel cobalt oxide precursor / nickel foam composite electrode was calcined in a tube furnace under air conditions at a temperature of 370°C, a heating rate of 5°C / min, and a holding time of 1.5 hours. After calcination, it was placed in anhydrous ethanol and ultrasonicated for 30 seconds to remove the loosely fixed debris on the electrode surface, and then thoroughly cleaned and vacuum dried at 70°C for 12 hours to obtain a dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode, recorded as NCO-w1 / NF.

[0037] Example 2: Preparation of dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode-2 (NCO-w2 / NF)

[0038] ① Dissolve 0.24g of NiCl2·6H2O, 0.48g of CoCl2·6H2O, 0.025g of sodium dodecyl sulfate and 0.6g of urea in a mixed solvent of 30mL of ethanol and water, with a volume ratio of ethanol to water of 1:5, and stir thoroughly to make it uniform. Then transfer it to a reactor with a volume of 75mL, use a polytetrafluoroethylene disc with a gap to fix the nickel foam so that it stands vertically in the inner tank of the reactor, and hydrothermally react at 110°C for 6h. After the reaction, wash the nickel foam repeatedly with deionized water and ethanol, and vacuum dry it to obtain a nickel cobalt oxide precursor / nickel foam composite electrode;

[0039] ② The nickel cobalt oxide precursor / nickel foam composite electrode was calcined in a tube furnace under air conditions at a temperature of 370°C, a heating rate of 5°C / min, and a holding time of 1.5 hours. After calcination, it was placed in anhydrous ethanol and ultrasonicated for 30 seconds to remove the loosely fixed debris on the electrode surface, and then thoroughly cleaned and vacuum dried at 70°C for 12 hours to obtain a dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode, recorded as NCO-w2 / NF.

[0040] Example 3: Preparation of dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode-3 (NCO-w3 / NF)

[0041] ① Dissolve 0.24g of NiCl2·6H2O, 0.48g of CoCl2·6H2O, 0.125g of sodium dodecyl sulfate and 0.6g of urea in a mixed solvent of 30mL of ethanol and water, with a volume ratio of ethanol to water of 1:5, and stir thoroughly to make it uniform. Then transfer it to a reactor with a volume of 75mL, use a polytetrafluoroethylene disc with a gap to fix the nickel foam so that it stands vertically in the reactor liner, and hydrothermally react at 110℃ for 6h. After the reaction, wash the nickel foam repeatedly with deionized water and ethanol, and vacuum dry it to obtain a nickel cobalt oxide precursor / nickel foam composite electrode.

[0042] ② The nickel cobalt oxide precursor / nickel foam composite electrode was calcined in a tube furnace under air conditions at a temperature of 370°C, a heating rate of 5°C / min, and a holding time of 1.5 hours. After calcination, it was placed in anhydrous ethanol and ultrasonicated for 30 seconds to remove the loose debris on the electrode surface, then thoroughly cleaned and vacuum dried at 70°C for 12 hours to obtain a dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode, recorded as NCO-w3 / NF.

[0043] Comparative Example 1: Preparation of nickel cobalt oxide nanoneedle / nickel foam composite electrode

[0044] ① Dissolve 0.24g of NiCl2·6H2O, 0.48g of CoCl2·6H2O and 0.6g of urea in 30mL of deionized water and stir thoroughly to make it uniform. Then transfer it to a reactor with a volume of 75mL, use a polytetrafluoroethylene disc with a gap to fix the nickel foam so that it stands vertically in the reactor liner, and hydrothermally react at 110℃ for 6h. After the reaction, wash the nickel foam repeatedly with deionized water and ethanol, and vacuum dry it to obtain a nickel cobalt oxide nanoneedle precursor / nickel foam composite electrode.

[0045] ② The nickel cobalt oxide nanoneedle precursor / nickel foam composite electrode was calcined in a tube furnace under air conditions at a temperature of 370°C, a heating rate of 5°C / min, and a holding time of 1.5 hours. After calcination, it was placed in anhydrous ethanol for 30 seconds to remove the loosely fixed debris on the surface, and then thoroughly cleaned and vacuum dried at 70°C for 12 hours to obtain the nickel cobalt oxide nanoneedle / nickel foam composite electrode.

[0046] Comparative Example 2: Preparation of Nickel Cobalt Oxide Nanosheets / Nickel Foam Composite Electrode

[0047] ① Dissolve 0.24g of NiCl2·6H2O, 0.48g of CoCl2·6H2O and 0.6g of urea in a mixed solvent of 30mL of ethanol and water, with a volume ratio of ethanol to water of 2:1, and stir thoroughly to make it uniform. Then transfer it to a reactor with a volume of 75mL, use a polytetrafluoroethylene disc with a gap to fix the nickel foam so that it stands vertically in the reactor liner, and hydrothermally react at 110℃ for 6h. After the reaction, wash the nickel foam repeatedly with deionized water and ethanol, and vacuum dry it to obtain a nickel cobalt oxide nanosheet precursor / nickel foam composite electrode.

[0048] ② The cobalt oxide nanosheet precursor / nickel foam composite electrode was calcined in a tube furnace under air conditions at a temperature of 370°C, a heating rate of 5°C / min, and a heat preservation time of 1.5 hours. After calcination, it was placed in anhydrous ethanol for 30 seconds to remove the loosely fixed debris on the surface, and then thoroughly cleaned and vacuum dried at 70°C for 12 hours to obtain the cobalt oxide nanosheet / nickel foam composite electrode.

[0049] The electrodes prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested. In order to better characterize the material itself, the samples used in the four test methods of XRD, BET, TEM and EDS were powder samples collected by placing the composite electrode in ethanol for 2 hours of ultrasound and centrifugal drying. Example 1 (NCO-w1 / NF) was used as a test representative to perform the above characterization comparison with the comparative example. Five composite electrodes of Examples 1 to 3 and Examples 1 to 2 were used for SEM characterization and electrochemical performance testing. The instrument used for the electrochemical test was SOLARTRON constant potential and constant current instrument 1287A (USA Transmission Power), and the test system was a three-electrode system. The platinum sheet was used as the counter electrode, the reference electrode was mercury / mercury oxide (Hg / HgO), the electrolyte was a 2M potassium hydroxide aqueous solution, and the electrodes prepared in each embodiment and comparative example were clamped with a platinum sheet electrode clamp as the working electrode; the cyclic voltammetry test voltage range was 0-0.7V (relative to the mercury / mercury oxide reference electrode), the scan rate increased from 5mv / s to 80mv / s, the constant current charge and discharge test voltage range was 0-0.52V (relative to the mercury / mercury oxide reference electrode), and the current density increased from 1A / g to 10A / g. The results are as follows:

[0050] Figure 1 The XRD patterns of Example 1 and Comparative Examples 1 and 2 are shown in the figure. As shown in the figure, the dahlia-shaped nickel cobalt oxide nanowire clusters prepared by the present invention and the two comparative examples are all spinel structures, and their diffraction peaks are consistent with the standard card (PDF#20-0781). The peaks at 31.2°, 36.7°, 59.1°, and 64.9° correspond to the (220), (311), (511), and (440) crystal planes of nickel cobalt oxide, respectively, and no other significant impurity peaks appear, proving that the synthesized product is pure nickel cobalt oxide.

[0051] Figure 2 The SEM image of the surface of the dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode prepared in Example 1 of the present invention, the TEM image of a single nanowire and its EDS element distribution map. Figure 2 (A) and (B) are SEM images of the surface of the dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode. Figure 2 As shown in (A) and (B), the nickel cobalt oxide material grows on the electrode surface as a special structure resembling a dahlia, which is relatively rare in previous work. Further observation revealed that its overall structure is assembled from many nanowires with clear gaps between the nanowires, allowing most of the nanowires to be exposed to the electrolyte. Figure 2 (C) is a TEM image of a single nanowire. Figure 2The middle (C) shows that the diameter of the nanowire is about 80nm, and the nanowire itself is not a single crystal, but is composed of multiple smaller nanoparticles. There are also many holes between the particles, which will significantly increase the specific surface area of ​​the electrode material and thus improve its electrochemical performance. Figure 2 (D) EDS spectrum of a single nanowire, the EDS spectrum shows that the distribution of the three elements of nickel, cobalt and oxygen is very uniform, further proving the successful synthesis of nickel cobaltate. In addition, it is worth noting that in Examples 1-3 of the present invention, a small amount of ethanol can effectively increase the coverage of the electrode material on the nickel foam. If no ethanol is added and water is used alone as a solvent, a dahlia-like morphology can also be obtained, but under this condition, the morphological structure synthesized by the present invention has a poor coverage effect on the surface of the nickel foam.

[0052] Figure 3 The surface SEM image of the dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode-2 (NCO-w2 / NF) prepared in Example 2 shows that when the concentration of sodium dodecyl sulfate is low, the nanowires grow more disorderly, some nanowires grow insufficiently, and only a small number of nanowires can be aggregated into a cluster structure similar to a flower pattern. More nanowires can only be aggregated into spiked rods, and a large number of nanowires cannot be stretched out due to stacking, which may have an adverse effect on the electrochemical performance.

[0053] Figure 4 The surface SEM image of the dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode-3 (NCO-w3 / NF) prepared in Example 3 shows that when the concentration of sodium dodecyl sulfate is high, the size and stacking number of the patterned nanowire clusters increase significantly. Compared with Example 2, the pattern structure is very clear, proving that increasing the amount of sodium dodecyl sulfate added can effectively improve the phenomenon of irregular aggregation of nanowires. However, compared with Example 1, too many pattern clusters are stacked and aggregated on each other, resulting in a problem similar to that of Example 2: the nanowires cannot be fully exposed.

[0054] Figure 5 The surface SEM image of the nickel cobalt oxide nanoneedle / nickel foam composite electrode prepared in Comparative Example 1, the TEM image of a single nanoneedle and its EDS element distribution map. Figure 5 (A) and (B) are SEM images of the composite electrode surface. As shown in the figure, the nanoneedles are arranged in a disorderly direction on the surface of the nickel foam, and their diameter gradually decreases from the root to the tip. Figure 5 (C) is a TEM image of a single nanoneedle. Figure 5 As can be seen in (C), the diameter of a single nanoneedle is about 170 nm, which is significantly larger than that of Example 1 of the present invention; Figure 5 The EDS element distribution diagram of a single nanoneedle in (D) also proves that the element distribution of the comparison sample is also very uniform.

[0055] Figure 6 The surface SEM image of the nickel cobalt oxide nanosheet / nickel foam composite electrode prepared in Comparative Example 2, the TEM image of a single nanosheet and its EDS element distribution map. Figure 6 (A) and (B) are SEM images of the composite electrode surface, with the nanosheets arranged vertically on the nickel foam surface; Figure 4 Middle (C) is a transmission electron microscope image of a large-sized nanosheet. Although the planar size is large, its thin thickness can provide a larger specific surface area than that of comparative example 1, and may show more excellent electrochemical performance; Figure 6 (D) is the EDS element distribution diagram of the nanosheet, which also proves that the element distribution of the comparison sample is also very uniform.

[0056] Figure 7 (A), (B), and (C) are the specific surface area and pore size analysis (BET) diagrams of Example 1 of the present invention and Comparative Examples 1 and 2, respectively. The adsorbed gas is nitrogen. The results show that they belong to the IV type isotherm, indicating that the materials prepared in Example 1 and Comparative Examples 1 and 2 have porous properties. The calculation results of the multi-point BET method show that, thanks to the smaller structural size, Example 1 of the present invention has a pore size of 57.6 m 2 / g, which is larger than the 40.6 m 2 / g and 52.8m 2 / g. The inset is a pore size distribution diagram obtained based on the BJH method. The pore sizes of the three examples are all distributed in the range of 0-20nm. The average pore size of Example 1 of the present invention is 14.3nm, and that of Comparative Examples 1 and 2 is 18.4nm and 17.7nm respectively. The results show that the dahlia-shaped nickel cobalt oxide nanowire cluster structure of the present invention has a larger specific surface area, can provide more electrochemical active sites, is conducive to the full infiltration of the electrolyte, and facilitates ion transfer, thereby obtaining better electrochemical performance.

[0057] Figure 8 (A) and (B) are respectively the cyclic voltammetry scanning diagram (CV) and the constant current charge-discharge diagram (GCD) of Example 1 of the present invention. As can be seen from the figure, the CV curve shows a pair of obvious redox peaks, which is a typical Faraday reaction, indicating that it has good pseudocapacitive properties. As the scan rate increases, the redox peaks move over the positive and negative potentials, respectively, and the complete redox peak type can still be maintained at a high scan rate, which shows that the material has good redox reaction kinetics and rate performance. The constant current charge-discharge curve shows that there is a pair of obvious charge-discharge platforms at each current density, which corresponds well to the redox peak potential of the CV diagram.

[0058] Fig. 9It is a constant current charge and discharge diagram of Examples 1 to 3 of the present invention and Comparative Examples 1 to 2 at a current density of 1 A / g. It can be seen from the figure that Example 1 has the longest discharge time. Through calculation, it is known that its specific capacitance is 1191F / g. The specific capacitances of Examples 2 to 3 and Comparative Examples 1 to 2 are 1134F / g, 1111.8F / g, 995.3F / g and 1142F / g, respectively; Example 1 of the present invention has the best performance.

[0059] Fig.10 The graphs of the mass specific capacity (Cs) of the composite electrodes prepared in Examples 1 to 3 and Comparative Examples 1 to 2 as a function of current density are shown. The curves of Examples 1 to 3 of the present invention are all higher than those of Comparative Example 1, except that Example 2 is slightly lower than Comparative Example 2 at certain current densities. This is because the low amount of sodium dodecyl sulfate added results in poor nanowire growth, and no clear dahlia-shaped nanowire clusters have been formed, resulting in the inability to fully expose the electrochemical active sites. Example 1 is higher than all other examples at all current densities, further demonstrating its excellent rate performance and the beneficial effects provided by the special structure.

[0060] In summary, after testing and analysis, compared with Examples 2 to 3 and Comparative Examples 1 to 2, Example 1 has the best performance and is the most preferred embodiment of the present invention. The dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode prepared in Example 1 of the present invention has high purity and special morphology and structure. Thanks to the high surface area of ​​57.6 m2 / g and the porous structure, it has a high specific capacitance of 1192 F / g at a current density of 1 A / g. Compared with the common needle and sheet structures, its rate performance is also better, providing a new method for preparing special pattern structures by nanowire self-assembly.

[0061] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention.

Claims

1. A method for preparing a dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode, characterized in that: The steps include: Step 1, washing and vacuum drying the nickel foam to obtain clean nickel foam; Step 2: Dissolve NiCl2·6H2O, CoCl2·6H2O, urea and sodium dodecyl sulfate in a mixed solvent of ethanol and water, stir evenly and transfer to a hydrothermal reactor, then add clean nickel foam and perform hydrothermal reaction to obtain a nickel cobalt oxide precursor / nickel foam composite electrode; Step 3: calcining the nickel cobalt oxide precursor / nickel foam composite electrode, and then washing and vacuum drying to obtain a dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode.

2. The preparation method according to claim 1, characterized in that: In step 2, the mass ratio of NiCl2·6H2O, CoCl2·6H2O, sodium dodecyl sulfate and urea is 0.24:0.48:(0.025-0.125):0.6; in the mixed solvent of ethanol and water, the volume ratio of ethanol to water is 1:

5.

3. The preparation method according to claim 1, characterized in that: In step 2, the conditions of the hydrothermal reaction are: the hydrothermal temperature is 110° C. and the hydrothermal time is 6 h.

4. The preparation method according to claim 1, characterized in that: In step 2, when the clean nickel foam is placed, the clean nickel foam is inserted into the gap of the polytetrafluoroethylene disc so that it stands vertically in the inner tank of the hydrothermal reactor to ensure that the mixed solvent completely immerses the nickel foam.

5. The preparation method according to claim 1, characterized in that: In step 2, the nickel cobalt oxide precursor / nickel foam composite electrode obtained by the hydrothermal reaction is naturally cooled, and the nickel foam is repeatedly rinsed with water and anhydrous ethanol, and dried in a vacuum drying oven; the drying temperature is 70° C., and the drying time is 12 hours.

6. The preparation method according to claim 1, characterized in that: Step 1 specifically comprises: cutting the nickel foam, ultrasonically cleaning it with hydrochloric acid, ethanol and deionized water in sequence, and vacuum drying it to obtain clean nickel foam; The nickel foam was cut to a size of 10 mm × 20 mm, the concentration of hydrochloric acid was 2 M, each ultrasonication time was 10 min, the drying temperature was 70 °C, and the drying time was 12 h.

7. The preparation method according to claim 1, characterized in that: In step three, the nickel cobalt oxide precursor / nickel foam composite electrode is placed in a tubular furnace and calcined under the following conditions: temperature 370° C., calcination atmosphere air, calcination time 1.5 h, and heating rate 5° C. / min.

8. The preparation method according to claim 1, characterized in that: In step three, the calcined composite electrode is placed in anhydrous ethanol for ultrasonic treatment for 30 seconds, and then washed and vacuum dried to obtain a dahlia-shaped nickel cobalt oxide nanowire cluster / nickel foam composite electrode; the drying temperature is 70° C., and the drying time is 12 hours.

9. A composite electrode prepared according to the preparation method according to any one of claims 1 to 8.

10. Application of the composite electrode prepared by the preparation method according to any one of claims 1 to 8, characterized in that: For use in supercapacitors.